Rifting and seafloor spreading in the South China sea: a subduction-related extension on the down-going plate? - Chang, Sung-Ping; Pubellier, Manuel (Comptes Rendus. Géoscience)
Active margins are sensitive to several subduction-related processes which include rapid opening and closure of neighboring basins. The stages of rifting, spreading and the cessation, of activity the South China Sea basin in Cenozoic appears to be coeval with the progressive closure of the Proto-South China Sea which ended with collision in Borneo and Palawan. The evolution bracketed between 45 Ma and 16 Ma, migrated through time from NE to SW. This dual simultaneous tectonic evolution illustrates how far-field subduction process may impact the regional tectonics in terms of both rifting and contraction of the crust from initiation to termination.